Initial Phase Angle Detection of Permanent Magnet Synchronous Linear Motor Based on Spectrum Observer - Chengmei LIN; Zhentian LIU; Guangsen WANG; Liang ZHOU; Youxing XIONG (机车电传动)
In order to solve the problems of complex algorithm and high performance requirement of hardware circuit in the existing initial phase angle detection method of permanent magnet synchronous linear motor, a new method of PMSM initial phase angle detection based on spectral observer was proposed. By applying DC voltage vector, the motor was positioned near a specified angle. On the basis of the position loop controlling the motor displacement to zero, a sinusoidal jitter of fixed amplitude was applied to the estimated angle to obtain the quadrature current waveform. According to the theory of spectral observer, the first-order fraction of the cross-axis current waveform was obtained by filtering and observing, and the estimated angle deviation was obtained by calculating the zeros of the first-order fraction. Finally, the rapid control prototype of permanent magnet synchronous linear motor was built using RT-LAB simulation platform. The experimental results verified the correctness and effectiveness of the proposed method.